The occurrence and distribution of phenylnaphthalenes, terphenyls and quaterphenyls in selected lacustrine shales and related oils in China. (May 2016) - Li, Meijun; Wang, Hui; Shi, Shengbao; Fang, Ronghui; Tang, Qi; Wang, Daowei
Highlights: Terphenyls and quaterphenyls are identified in oils and rock extracts. The occurrence of phenyl PAHs and polyphenyls in lacustrine shales is reported. The effect on relative abundance of isomers is discussed. A maturity indicator related to terphenyls is proposed. Abstract: Phenylnaphthalenes (PhNs), terphenyls (TrPs), quaterphenyls (QtPs) and triphenylbenzenes were identified by the use of authentic standards in GC–MS analysis. Phenyl derivatives of fused ring polycyclic aromatic hydrocarbons (PhPAHs) and polyphenyls (PPhs) were observed in selected lacustrine shales and related oils from the Tarim, Liaohe and Bebuwan Basins in China. All isomers of phenylnaphthalene and terphenyl were observed in these oils. The more stable 2-PhN and m -Trp, p -TrP isomers are predominant among phenylnaphthalenes and terphenyls, respectively. The effect of maturity on the distribution patterns of phenylnaphthalenes and terphenyls in a set of lacustrine shales from the Liaohe Basin, East China was investigated. The depth trends of three currently used maturity indicators were investigated. Analysis was based on the relative abundance of phenylnaphthalene and terphenyl isomers, namely PhNR (2-PhN/1-PhN), TrP1 ( p -TrP/ o -TrP) and TrP2 (( m -TrP+ p -TrP)/ o -TrP) in lacustrine shales from well S202 in the Liaohe Basin, East China. The indicators increase slightly with relatively great deviations within low to intermediate maturation stages and then increase abruptly in high maturity stages. Therefore, they are not suitable maturity indicators for lacustrine source rocks in this study. An alternative thermal maturity indicator, defined as p -TrP/ m -TrP was proposed. It exhibits a uniform increase with increasing maturity and is probably a more suitable indicator for use in maturity assessment in lacustrine source rocks and related oils. This study broadens the current understanding of the occurrence and distribution of PhPAHs and PPhs in sedimentary organic matter of various origins.